Complete Genome Sequence of Rothia mucilaginosa DY-18: A Clinical Isolate with Dense Meshwork-Like Structures from a Persistent Apical Periodontitis Lesion. (3rd October 2010) - Yamane, Kazuyoshi; Nambu, Takayuki; Yamanaka, Takeshi; Mashimo, Chiho; Sugimori, Chieko; Leung, Kai-Poon; Fukushima, Hisanori
Abstract : Rothia mucilaginosa is an opportunistic pathogen in the human oral cavity and pharynx. We found that R. mucilaginosa DY-18, a clinical isolate from a persistent apical periodontitis lesion, had biofilm-like structures. Similar structures were also observed on R. mucilaginosa ATCC25296. To further study these structures, we determined the complete genome sequence of DY-18 and found it a 2.26-Mb chromosome. Regarding stress responsive systems known to affect biofilm formation in many bacteria, DY-18 genome possessed only two sigma factor genes. One of these encoded an additional sigma factor whose promoter-binding activity may be regulated in response to environmental stimuli. Additionally, several genes assigned to two-component signal transduction systems were presented in this genome. To the best of our knowledge, this is the first complete genome of R. mucilaginosa species and our data raise the possibility that this organism regulates the biofilm phenotype through these stress responsive systems.